Share on vk Share on google_plusone_share Share on twitter Share on email More Sharing Services The distribution of letter doublets in the Apostolus Christinopolitanus of the 12th century - A.A. Toksubaeva (Ученые записки Казанского университета: Серия Гуманитарные науки, 2022)
This article considers the graphic and orthographic features of the Apostolus Christinopolitanus dated to the 12th century. The manuscript is of Galician-Volynian origin. It contains a liturgical text and is distinguished by an archaic style and numerous examples of East Slavic spellings. Hence, its spelling system, especially the letter doublets and their allographs, is of particular interest. Here, the graphic and orthographic features of the Apostolus Christinopolitanus were studied on the basis of the color photocopies of the Lviv and Kyiv parts, as well as on its electronic machine-readable edition. The analysis was carried out using corpus management software tools and information on the distribution of certain graphemes and their allographs during the 11th and 12th centuries. It was revealed that the scribe adhered to a clear writing sequence characterized by strict differentiation of variant markings in each of the considered doublets, but he used all variants of spelling known to him, which is evidence of his professionalism. The strict differentiation of the spelling variants in each of the doublet links is a characteristic feature of the Apostolus Christinopolitanus.